2018
DOI: 10.1155/2018/1067134
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR-ADAM17 Axis in Chronic Obstructive Pulmonary Disease and Cystic Fibrosis Lung Pathology

Abstract: Chronic obstructive pulmonary disease (COPD) and cystic fibrosis (CF) share molecular mechanisms that cause the pathological symptoms they have in common. Here, we review evidence suggesting that hyperactivity of the EGFR/ADAM17 axis plays a role in the development of chronic lung disease in both CF and COPD. The ubiquitous transmembrane protease A disintegrin and metalloprotease 17 (ADAM17) forms a functional unit with the EGF receptor (EGFR), in a feedback loop interaction labeled the ADAM17/EGFR axis. In ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 239 publications
(346 reference statements)
1
26
1
Order By: Relevance
“…Viral infection per se also activates EGFR and EGFR signaling to ERK1/2, while STATs control the severity of HRV mediated airway inflammation. In vitro, HRV induced goblet cell hyperplasia was demonstrated to function through NF-κB-dependent MMP-mediated TGF-α release, leading to EGFR activation and mucus secretion (97). Interestingly, virusinduced EGFR activation suppressed interferon regulatory factor 1 (IRF1)-dependent IFN-λ airway epithelial antiviral signaling (98, 99).…”
Section: Tlr Sensing and Egfr Signalingmentioning
confidence: 99%
“…Viral infection per se also activates EGFR and EGFR signaling to ERK1/2, while STATs control the severity of HRV mediated airway inflammation. In vitro, HRV induced goblet cell hyperplasia was demonstrated to function through NF-κB-dependent MMP-mediated TGF-α release, leading to EGFR activation and mucus secretion (97). Interestingly, virusinduced EGFR activation suppressed interferon regulatory factor 1 (IRF1)-dependent IFN-λ airway epithelial antiviral signaling (98, 99).…”
Section: Tlr Sensing and Egfr Signalingmentioning
confidence: 99%
“…Basic fibroblast growth factor (bFGF or FGF2) is a potent mitogen for many cell types, including airway smooth muscle cells, fibroblasts, and endothelial cells [ 107 ]. FGF2 can be released from inflammatory cells including T lymphocytes, eosinophil, mast cells, macrophages, and myeloid dendritic cells [ [108] , [109] , [110] ]. FGF carry out multiple biological processes by signalling through FGF receptors, including tumor angiogenesis, embryonic development, differentiation, proliferation, migration, and injury repair [ [111] , [112] , [113] ].FGF2 generate innate immune response by stabilizing retinoic acid-inducible gene-I (RIG-I) and preventing proteasome-mediated RIG-I degradation( 114 ).…”
Section: The Hepatocyte Growth Factor (Hgf)mentioning
confidence: 99%
“…Studies show that diabetes, cardiovascular diseases, obesity, and other comorbidities are risk factors for COVID-19 [48] , [49] . When what these comorbidities have in common is analyzed, it is observed that individuals affected by these comorbidities have a higher expression of ADAM17 [50] , [51] , [52] , [53] . ADAM17 is a protease with a single transmembrane domain and a cytoplasmic portion.…”
Section: Hypothesismentioning
confidence: 99%